The Arctic Geo-Economy: Mobility of Strategic Oil Resources at the End of Globalization - Sergey Yu. Kozmenko; Arina S. Kozmenko (Арктика и Север, 2022)
A distinctive feature of the cyclical dynamics of global development is the rapid transformation of the maxim of “global superiority” into softer forms of leadership on the geopolitical and economic atlas of the modern world, such as “national power” and/or “regional advantage”. This requires a concentration of resources to achieve the latter's mobility on the strategic movement trends of contemporary Russia. The importance of oil and petroleum products in the formation of the Russian Federal Budget and the National Welfare Fund cannot be overestimated. Today, oil is essentially the main source for the successful implementation of the special military operation and, at the same time, ensuring the progressive development of Russia. The article substantiates the necessity to maintain the economic turnover of oil resources development, including in the Arctic, carries out an expert assessment of three options for the development of oil production: reduction of production; reduction of oil exports against the background of increasing domestic consumption; and ensuring the mobility of export supplies to find and develop new markets.